APLIKASI PENGGUNAAN KOTORAN PUYUH DAN AMPAS TAHU TERFERMENTASI UNTUK MEDIA PEMELIHARAAN CACING SUTERA DI UPR D5 DESA SUKA PINDAH KABUPATEN OGAN ILIR - Yulisman, Yulisman; Jubaedah, Dade; Ismalia, Nova; Marsi, Marsi; Wijayanti, Marini; Mukti, Retno Cahya; Amin, Mohamad (Universitas Mataram, 2024)
Silk worms is commonly used as natural feed for larval on fish hatchery. Cultivating silk worms requires a substrate as well as a feed source to support their growth. Fermented quail manure, tofu waste, and tapioca flour can be utilized as cultivation media for silk worms. This activity aims to apply the use of fermented quail manure, and tofu dreg, and tapioca flour on the growth of silk worms at Unit Pembenihan Rakyat D5 Suka Pindah Village, Ogan Ilir, South Sumatera. This activity is community service through extension and silk worm culture using media from fermented quail manure and tofu dregs. Silk worm cultivation was carried out using a closed-flow water system with two containers, one for fermented media and one for non-fermented media. Silk worms 150 g m-3 were stocked and reared for 30 days. The results obtained from community extension are an increase in understanding of the target audience from quite good to good and very good. The result of the silk worm culture demonstration plot show that absolute biomass growth in the fermented media at 588.80 g m-2 compared to non-fermented media at 440.00 g m-2 Therefore, fish farmers can apply silk worm culture with fermented media to be able to provide natural feed of fish, independently.